2021
DOI: 10.1016/j.celrep.2021.110080
|View full text |Cite
|
Sign up to set email alerts
|

The protease SPRTN and SUMOylation coordinate DNA-protein crosslink repair to prevent genome instability

Abstract: Highlights d SUMOylation and ubiquitylation enable DPC repair during DNA replication d Resolution of ubiquitylated and SUMOylated DPCs requires the protease SPRTN d Inactivation of SUMOylation after DPC formation activates homologous recombination d DPC SUMOylation and SPRTN prevent recombinationdependent genomic instability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 68 publications
4
35
0
Order By: Relevance
“…It is therefore conjectured that, upon TOP-DPC SUMOylation and ubiquitylation by the Siz1–Slx5/8 pathway, the Cdc48 complex binds the heterologous SUMO–ubiquitin chain and unfolds TOP-DPCs to facilitate their digestion by Wss1. In mammalian cells, SUMOylation was shown to channel DPC repair pathway(s) to SPRTN, the ortholog of Wss1, during DNA replication ( Ruggiano et al, 2021 ). Unlike Wss1, SPRTN lacks SIM but is still able to interact with both ubiquitin and SUMO moieties conjugated to DPCs.…”
Section: Sumoylation In the Repair Of Topoisomerase-mediated Dna Damagementioning
confidence: 99%
“…It is therefore conjectured that, upon TOP-DPC SUMOylation and ubiquitylation by the Siz1–Slx5/8 pathway, the Cdc48 complex binds the heterologous SUMO–ubiquitin chain and unfolds TOP-DPCs to facilitate their digestion by Wss1. In mammalian cells, SUMOylation was shown to channel DPC repair pathway(s) to SPRTN, the ortholog of Wss1, during DNA replication ( Ruggiano et al, 2021 ). Unlike Wss1, SPRTN lacks SIM but is still able to interact with both ubiquitin and SUMO moieties conjugated to DPCs.…”
Section: Sumoylation In the Repair Of Topoisomerase-mediated Dna Damagementioning
confidence: 99%
“…A subsequent study further demonstrated the relative roles of SPRTN versus the proteasome in DPC repair in Xenopus egg extracts. It was found that SPRTN and the proteasome are distinct pathways that act independently from each other (Larsen et al, 2019 ; Ruggiano et al, 2021 ). SPRTN recruitment requires DPC SUMOylation (Ruggiano et al, 2021 ) and the presence of a DNA polymerase on one side and a short tract of ssDNA on the other side of a DPC in order to prevent indiscriminate destruction of replisome components and chromatin proteins (Larsen et al, 2019 ).…”
Section: Contribution Of Proteases To the Hallmarks Of Agingmentioning
confidence: 99%
“…Alternatively, if the polymerase extends the nascent DNA to within a few nucleotides of the lesion, SPRTN-mediated DPC proteolysis is activated to degrade modified or unmodified DPCs. The remaining peptide-DNA adduct can be bypassed by TLS polymerases and repaired post-replication ( Larsen et al, 2019 ; Sparks et al, 2019 ; Ruggiano et al, 2021 ). Created in BioRender.com .…”
Section: Mechanisms Of Dpc Repairmentioning
confidence: 99%
“…A recent study demonstrated that both DPC ubiquitination and SUMOylation promote DPC repair by SPRTN. DPC ubiquitination signals SPRTN recruitment to DPC sites and DPC SUMOylation prevents activation of HR to promote DPC repair by SPRTN ( Ruggiano et al, 2021 ). Thus, SPRTN promotes repair of unmodified, ubiquitinated, and SUMOylated DPCs.…”
Section: Mechanisms Of Dpc Repairmentioning
confidence: 99%
See 1 more Smart Citation